Estudio de factibilidad para la creación de una empresa productora y comercializadora de accesorios femeninos en la ciudad de Santiago de Cali (2014)
This feasibility study is titled "Creating a Producer and marketer of women's accessories business in the city of Santiago de Cali," offers women accessories women's craft as a complement to your wardrobe from day to day. The desire of this study to determine the feasibility , to accessories company believes and is recognized in the relevant market as one of the best companies that produce and sell handmade women accessories. The feasibility study is structured by chapters; The first chapter is concerning the problem statement , objectives , methodological design was carried out for the realization of the whole project and the primary and secondary sources of information. The second chapter concerns the general aspects of the environment , where each of these details . The third chapter is the study of market, where product identification , analysis of demand , supply analysis , price analysis and marketing and distribution of the products shown . Chapter four, technical study, refers to the general and specific conditions, such as size, location and engineering to be taken into account to start with the feasibility study. The last chapters deal with the analysis of the financial results of any feasibility study , conclusions and recommendations are made to the project after completing the study.